Acervo literário e software leitor : a crônica de Josué Guimarães (entre1980 a 1986) - Krug, Flavia Susana (2022)
The theme of this thesis is the interrelation between reading and technological devices, having as a corpus of analysis publications in the press produced by Josué Guimarães, in the period between 1981 and 1986, included in the Josué Guimarães Literary Collection (ALJOG/UPF), under the custody of the Universidade de Passo Fundo (UPF), as an integrating part of the infrastructure of the Postgraduate Program in Languages and the Institution's Languages Course. The present work has the purpose of contributing with considerations about the (re)reading of the original journalistic material, as well as discussing the results obtained in the exploration of the IRAMUTEQ digital platform, in a literary collection, via Word Cloud and Similitude Analysis resources. The main theoretical framework, on which the study is developed, is centered on the assumptions of Maria da Glória Bordini (2003, 2009, 2017), based on statements that make us ponder the real indispensability of materials protected in collections also depending on the mobilization to use technological resources to perpetuate them from aspired articulations either with literary works, or with historical works in general. In environments like this, texts and extra-texts come together. In this bias, when studying authors, works, facts, events and the like in collections, the essence of each construction, through existing technologies, is portrayed with more success and relational potential. As for the studies of Miguel Rettenmaier (2008), it is important to take advantage of his ideas about investigating through literary collections which, in the author's view, increases the capacity of (re)interpretation based on the variety of textuality related to the intellectual production of certain writers, as well as the documentary information that permeates its existence. It is in collections, especially literary ones, that memory is explored to its limit, and manuscripts reveal even much more than an author's hands were capable of writing. On the other hand, Alberto Cupanni (2017) exposes essential understandings, as well as important philosophical statements that go beyond the philosophy of technology. In order to cover technology as an inviting and thought-provoking product, its studies facilitate reflective debates and challenge the existence of new research on the subject, since it is seldom explored in Brazil. Lúcia Santaella (2013, 2014) contributes with important reflections about the propagation of digital spaces, especially regarding the media that currently favors the access to communication. In addition, she asserts about the current processes of communication taking place fluidly, as well as about the hypermobility that unfolds through objects, environments, bodies and minds. As for the IRAMUTEQ Software, research by Ana Maria Justo and Brigido Vizeu Camargo (2013) leads to the understanding and appreciation of reading performed on technological platforms in different and dynamic ways. Lúcia Santaella (2013) contributes with important reflections about the multiplication of digital spaces, especially regarding the media that currently favors the access to communication. In addition, she asserts about the current processes of communication taking place fluidly, as well as about the hypermobility that unfolds through objects, environments, bodies and minds. In addition, the authors' observations on the IRAMUTEQ Software contribute to the perception of the agility and efficiency offered by the program in order to provide new perspectives on the observance of a texture, as well as the rigor of the qualitative textual data analysis performed by it. The research fits into the qualitative perspective of the descriptive-exploratory type. The corpus consists of 93 (ninety-three) texts, classified under the name passive production, items published in the press and examined from readings and singular observations, in addition to meticulous preparation for forwarding them to the selected program. The research is not intended to create interpretative models, yet it has the purpose of socializing a closer look at the journalistic production of Josué Guimarães in a period that registers significant marks in the political and social scenario in Brazil. The result of the exploration of the chronicles sent to IRAMUTEQ aims to demonstrate the essence of the thinking of the writer and journalist Josué Guimarães, experienced in the context of the period from 1980 to 1986.